New tool for internal pressure during fabrication and installation of mechanically lined pipelines using reel-lay method. (June 2016) - Tianfeng, Zhao; Zhigang, Tian
Highlights: A new approach to spool mechanically lined pipeline on a reel for pipe installation. Supporting sealing devices and an operation process are proposed. Application effects are simulated and predicted using finite-element models. The prototype test for 5-in. MLP packers is performed to verify the feasibilities of the device and the approach proposed. Abstract: As an ideal use of corrosion-resistant alloys and low-alloy steels, Mechanically Lined Pipelines (MLPs) have been employed gradually for offshore exploitation. If the risk of thin-walled liner wrinkling is to be effectively averted, reel-lay is the most economical installation method for this type of pipeline, especially for deepwater oil and gas development. A suite of tools and corresponding techniques is proposed in this paper to realize the spooling-on of an MLP stalk with inner pressure to avoid detachment and wrinkling of the MLP liner. Additionally, The related numerical verification and a prototype test for a 5-in. MLP spooling-on tool are completed to prove the validity of this new technique and further illustrate the application effect of providing internal pressure during the spooling-on of MLP stalk to a reel.